Econometric Analysis of Supply and Demand for Log and Sawn Timber in Sabah - Mais, Kinus (1992)
This study investigates the main factors affecting supply and demand of log and sawn timber of Sabah. The partial adjustment and adaptive expectation (PAAE) frameworks for log and sawn timber were developed and estimated using time series data. The regression results and simulation tests indicate that the estimated models are satisfactory. All the significant coefficients have the correct signs. The Root Mean Square Percentage Error (RMSPE) and Theil inequality Coefficient values of the estimated models are low. The finding sindicate that the long run supply elasticity value with respect to logged area is low (0.19). On the contrary the factors influencing domestic demand for log are elastic. The long run domestic demand elasticity value with respect to domestic price and construct ion activities are -1.23 and 2.43 respectively. In the world market, log export demand is influenced by export price and construct ion activities of industrial countries. The long run export demand elasticity value with respect to export price and industrial construct ion activities are (-7.61) and (3.34) respectively. In the sawn timber market, the long run supply elasticity value with respect to domestic price, log input price,saw milling recovery rate and dummy variable for government incentives are 5.23, -0.79, 0.64, and 0.5 1 respectively. On the domestic demand side, only the construction activity is found to have an influence o n the quantity demanded. The long run domestic demand elasticity with respect to this variable is 7.54. Meanwhile in the world market, the long run export demand elasticity value with respect to export price, real effective exchange rate, construct ion activities of industrial countries and world economic recession are -4.00, -1.32, 4.21 and -0.35 respectively. The regression results revealed that the government policy to reduce logging area does not seem to have a substantial impact on the supply of logs. Also indirectly, log export royalty and restriction ion policies could influence log export volume(ceteris peribus). The government incentives such as low royalty rates on logs utilised domestic ally can encourage further down stream processing.